Dynamics of Change in Mangrove Forest Cover as a Protected Area Using Satellite Image on Peleng Island, Central Sulawesi - Mohammad Malik; Kuncahyo, Budi; Puspaningsih, Nining (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2023)
Mangrove forest is an important ecosystem supporting the life activities of coastal communities because it has various functions so it is very vulnerable to various disturbances. This problem is an important factor in the decline in the ability of mangroves to maintain the stability of the coastal ecosystem. Therefore, it is necessary to monitor and evaluate the dynamics of mangrove cover change in a spatio-temporal manner using remote sensing methods. Landsat imagery with a spatial resolution of 30 m was chosen as a data source to analyze the dynamics of mangrove forest cover. The purpose of the study was to measure, map and estimate the area of mangrove cover in 2019 and build a guided classification of mangrove cover changes in 2029 to estimate changes in mangrove forest cover, vegetation analysis to calculate diversity values and the Markov chain method using software. Stella. The results showed that the value of mangrove vegetation diversity in the belta strata was higher than the tree strata. Based on the significance value according to the criteria of ecosystem stability, it shows that the mangrove vegetation on Peleng Island is in the medium category and quite stable. Mangrove forests have continued to decline by 10.21% from 1999 to 2019, and in 2029 it is predicted that the area will continue to decline if this condition is left without any government policies that regulate it. Keywords: Dynamics, diversity, Landsat, mangroves, Peleng Island